2018
DOI: 10.1042/bsr20171379
|View full text |Cite
|
Sign up to set email alerts
|

The role of radical prostatectomy for the treatment of metastatic prostate cancer: a systematic review and meta-analysis

Abstract: The recommended therapy by EAU guidelines for metastatic prostate cancer (mPCa) is androgen deprivation therapy (ADT) with or without chemotherapy. The role of radical prostatectomy (RP) in the treatment of mPCa is still controversial. Hence, a meta-analysis was conducted by comprehensively searching the databases PubMed, EMBASE and Web of Science for the relevant studies published before September 1st, 2017. Our results successfully shed light on the relationship that RP for mPCa was associated with decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…Whether these theories apply to all or only specific solid tumors remain still to be determined. As pointed out by the results of our study, cytoreductive prostatectomy could have the potential to enhance mCRPC disease control 43,44 , but the lack of randomized controlled trials and the low level of evidence in the current literature preclude any firms conclusion on the benefit of cytoreductive strategy in mCRPC and to clearly identify the patients who would most benefit from their primary PCa ablation. Further, ongoing phase II and future phase III studies are mandatory to gain better insight in this regard.…”
Section: Role Of Primary Tumor Cytoreduction In Mcrpcmentioning
confidence: 83%
“…Whether these theories apply to all or only specific solid tumors remain still to be determined. As pointed out by the results of our study, cytoreductive prostatectomy could have the potential to enhance mCRPC disease control 43,44 , but the lack of randomized controlled trials and the low level of evidence in the current literature preclude any firms conclusion on the benefit of cytoreductive strategy in mCRPC and to clearly identify the patients who would most benefit from their primary PCa ablation. Further, ongoing phase II and future phase III studies are mandatory to gain better insight in this regard.…”
Section: Role Of Primary Tumor Cytoreduction In Mcrpcmentioning
confidence: 83%
“…However, for prolong survival for patients, many complements like new agents (including abiraterone, cabazitaxel, enzalutamide, and sipuleucel-T), local RT for oligo-metastatic disease, directed RT to metastases and RP for local tumor has emerged. Owing to improvement in surgical techniques, surgery as an intervention has changed from the treatment of choice in low risk to more advanced and even in high-risk PCa (26). Though present metaanalyses showed that LT significantly improved OS and CMS of patients with metastatic prostatic cancer (12,27), however, these meta-analyses lack a subgroup analysis of M1 substagespecific which often combine with highest risk and mortality.…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, a multivariable competing risk regression analyses tested CSM after propensity score matching in SEER database and the results showed that in comparison to RT, RP demonstrated important and statistically significant survival benefit in CSM in every stage of metastatic Pca (15). Additionally, Wang et al reported that a relatively low level of Gleason score, Mstage or N-stage could be a better prognosis for patients with metastatic Pca undergoing RP (26). Loppenberg et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although, we had successfully demonstrated the feasibility and survival benefit of LT for mPCa in improving OS or decreasing CSM, ACM, not all patients were suitable for it. Previous studies by Fossati et al and Wang et al revealed that patients with a relatively lower level of tumors and better general health seemed to benefit the most (35,36). Moreover, in a short period of time, no survival benefits have been observed for patients treated with RP compared with patients treated with androgen deprivation treatment (29).…”
Section: Discussionmentioning
confidence: 95%